PENGEMBANGAN BADAN USAHA MILIK DESA PEKAN TEBIH KEPENUHAN HULU KABUPATEN ROKAN HULU - Resky Afrianti; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
BUMDes is a village business formed / established by the village government whose capital ownership and management is carried out by the village government and the community with types of businesses in the form of village economic services such as, business services (microfinance transportation services, communication services, construction services, and energy services) , distribution of nine staples, sugar, salt, cooking oil, soybeans, and other foodstuffs managed through village stalls or village granaries), trade in agricultural products, and industry and folk handicrafts.This research focuses on the BUMDes development strategy with the aim of describing and analyzing how the development carried out by BUMDes and discovering the supporting and inhibiting factors in the BUMDes development process. The theory used in this study is the theory of Tyagi in Wibowo which states that organizational development is a planned, systematic, organized and collaborative effort in which the principles of knowledge about behavior and organizational theory are applied with the intention of improving the quality of life which is reflected in improving health and organizational vitality, increasing intensity of organization and group members in competence and self-esteem and the better society in general.The research method used is qualitative descriptive with data collection techniques through interviews, observation, and documentation. The selection of research informants using snowball sampling techniques. The results of this study indicate that in this study, problems were found that became the problem of the development of BUMDesPekanLebihLebih, both from internal factors related to human resources who were not yet competent in their fields, plus the program of the bumdes week program focused more on the savings and loan sector, so there was a buildup of money on the utilization of the bumdes so many loan surges were soaring. Key word: organization Development BUMDes Pekan Tebih